DEVELOPING STUDENT THINKING THROUGH METHODS USED OUTSIDE THE CLASSROOM. (Ustozlar uchun, 2024)
Abstract: In the article, the necessary information and sources are given about the tasks of interactive methods, innovative technologies, special features of interest in the use of pedagogical and information technologies in the educational process.